Asthma, symptoms of chronic bronchitis and ventilatory capacity among cobalt and zinc production workers. - Roto, Pekka (Scandinavian Journal of Work, Environment & Health, 1980)
This epidemiologic study was designed to determine whether occupational exposures to cobalt and zinc in the metallurgic industry increase the risk of asthma and symptoms of chronic bronchitis or decrease ventilatory capacity. The results indicated that, already at concentrations under 0.1 mg/m3, cobalt sulfate exposure increased the risk of asthma by about five times in exposed workers. The mechanism of sensitization was not studied further in this project. Neither zinc exposure nor sulfuric acid caused asthma or any other pulmonary impairments. All of the exposed groups had a highly significant chronic production of phlegm. This symptom was associated with smoking. Cobalt and sulfur workers had significantly more wheezing than the referents. The high frequency of this symptom probably reflected bronchial irritation caused by sulfur dioxide and cobalt sulfate. There was no evidence confirming that cobalt sulfate would have caused persistent bronchial obstruction or increased the risk of chronic bronchitis at the concentrations measured. Cobalt and/or sulfur dioxide exposure probably increased bronchial reactivity to methocholine transiently, but this effect did not last for more than 2 d. The prevalence of chronic bronchitis was between 0 and 2% in the exposed groups and 0% among the referents. There was no evidence that any exposure other than smoking would have caused chronic bronchitis. The Vmax50 meaurements did however indicate that sulfur dioxide and dusts probably increase the risk of chronic bronchitis gradually after more than 5 to 8 a of exposure at concentrations between 1--5 ppm (cm3/m3).
Keywords: asthma; chronic bronchitis; cobalt production worker; symptom; ventilatory capacity; zinc production worker